Optimasi Pembuatan Pellet Rumput Gajah (Pennisetum purpurium) sebagai Peluang Ekspor untuk Pakan Ternak Ruminansia - Winarto Winarto; Nani Irwani; Suraya Kaffi (Jurnal Ilmiah Teknik Pertanian - TekTan, 2014)
The objectives of this research are to determine the quality of a given base material pellet steam treatment or blanching, determine the formulation of water use for the process of making elephant grass pellets to reach Pelleting Durability Index (PDI) of 100%, and measure the effectiveness of elephant grass pellets to the performance of large ruminants. The results of the research are obtained that the elephant grass (Pennisetum purpureum) with steam treatment 100ÂºC for 5 minutes and drying in the sun contains 36.51% crude fiber, crude protein 10.5%, energy metabolism of 4,826 kcal/kg, crude fat 1.8 %, water content 85.8%, 2.8% ether extract. ash content of 12.5%, 1.5% calcium and 0.4% phosphorus. The addition of water 10% of the weight of the material gives the best performance and value pellets made pellet durability index (PDI) was 100%. Milk production of elephant grass pellets giving treatment was higher (11.67 liters/day) compared to fresh grass treatment (10.5 liters/day) was significantly different at 5% level. Similarly, the parameters of the milk fat content in treatment provision elephant grass pellets (3.8%) was significantly different at 5% level by treatment giving fresh elephant grass (3.37%), while the phosphorus content, kalsium.laktosa, protein, and vitamin C did not happen the real difference between the two treatments.Â  Keywords: pellets, elephant grass, feed efficiency, animal performance